Lipid Nanoparticles as a Promising Drug Delivery Carrier for Topical Ocular Therapy-An Overview on Recent Advances - Shery Jacob; Anroop B. Nair; Jigar Shah; Sumeet Gupta; Sai H. S. Boddu; Nagaraja Sreeharsha; Alex Joseph; Pottathil Shinu; Mohamed A. Morsy (MDPI AG, 2022)
Due to complicated anatomical and physical properties, targeted drug delivery to ocular tissues continues to be a key challenge for formulation scientists. Various attempts are currently being made to improve the in vivo performance of therapeutic molecules by encapsulating them in various nanocarrier systems or devices and administering them via invasive/non-invasive or minimally invasive drug administration methods. Biocompatible and biodegradable lipid nanoparticles have emerged as a potential alternative to conventional ocular drug delivery systems to overcome various ocular barriers. Lipid-based nanocarrier systems led to major technological advancements and therapeutic advantages during the last few decades of ocular therapy, such as high precorneal residence time, sustained drug release profile, minimum dosing frequency, decreased drug toxicity, targeted site delivery, and, therefore, an improvement in ocular bioavailability. In addition, such formulations can be given as fine dispersion in patient-friendly droppable preparation without causing blurred vision and ocular sensitivity reactions. The unique advantages of lipid nanoparticles, namely, solid lipid nanoparticles, nanostructured lipid carriers, nanoemulsions, and liposomes in intraocular targeted administration of various therapeutic drugs are extensively discussed. Ongoing and completed clinical trials of various liposome-based formulations and various characterization techniques designed for nanoemulsion in ocular delivery are tabulated. This review also describes diverse solid lipid nanoparticle preparation methods, procedures, advantages, and limitations. Functionalization approaches to overcome the drawbacks of lipid nanoparticles, as well as the exploration of new functional additives with the potential to improve the penetration of macromolecular pharmaceuticals, would quickly progress the challenging field of ocular drug delivery systems.